Anorexia nervosa is associated with higher brain mu-opioid receptor availability - Pak, Kyoungjune; Tuisku, Jouni; Karlsson, Henry K.; Hirvonen, Jussi; Rebelos, Eleni; Pekkarinen, Laura; Sun, Lihua; Latva-Rasku, Aino; Helin, Semi; Rajander, Johan; Karukivi, Max; Nuutila, Pirjo; et al. (Molecular psychiatry, 2025)
Anorexia nervosa (AN) is a severe psychiatric disorder, characterized by restricted eating, fear to gain weight, and a distorted body image. Mu-opioid receptor (MOR) functions as a part of complex opioid system and supports both homeostatic and hedonic control of eating behavior. Thirteen patients with AN and thirteen healthy controls (HC) were included in this study. We measured (1) MOR availability with [ 11 C]carfentanil positron emission tomography (PET), (2) brain glucose uptake (BGU) with 2-deoxy-2[ 18 F]fluoro-D-glucose ([ 18 F]FDG) PET during hyperinsulinemic-euglycemic clamp and (3) blood-oxygen-level-dependent signal with functional magnetic resonance imaging. All subjects underwent a screening visit consisting of physical examination, anthropometric measurements, fasting blood samples, an oral glucose tolerance test, psychiatric assessment, and an inquiry regarding medical history. Body fat mass (%) was measured and M value was calculated. MOR availability from caudate and putamen was higher in patients with AN and those from nucleus accumbens (NAcc) and thalamus showed the higher trend in patients with AN. There was no area where MOR availability was lower in patients with AN. BGU was not different between AN and HC. MOR availability and BGU were negatively correlated in caudate, NAcc and thalamus and showed the trend of negative association in putamen. In conclusion, AN is associated with higher MOR availability in the brain regions implicated in reward processing, while BGU remains unaltered. Therefore, the endogenous opioid system might be one of the key components underlying AN. This better understanding of AN could support the development of new treatments for AN.